An Escalating Dose “Binge” Model of Amphetamine Psychosis: Behavioral and Neurochemical Characteristics - Segal, David S. (J Neurosci, 1997)
Stimulant-induced psychosis is most frequently associated with a chronic, high-dose, multiple daily (“binge”) exposure pattern of stimulant abuse. To simulate these conditions, rats were exposed to escalating doses of amphetamine (Escalating Dose phase, 1.0–8.0 mg/kg) before multiple daily injections of relatively high doses of the drug (Run phase, 8.0 mg/kg/2 hr × 4 injections). Behavior was monitored continuously during the course of these treatments as well as during subsequent amphetamine challenges at various times after discontinuation of drug treatment. With the Escalating Dose–Run pattern of administration, a unique behavioral profile emerged in which tolerance occurred to the amount of time spent engaged in continuous focused stereotypy simultaneous with a profound increase in ambulatory activity that appeared agitated and disorganized. Parallel in vivo microdialysis studies showed progressively declining extracellular dopamine and serotonin responses, both within and between successive runs, whereas the norepinephrine response remained relatively unaltered. We propose that this model more closely resembles clinical manifestations of amphetamine psychosis and that the alterations may reflect a shift in the relative activation of mesolimbic and nigro-striatal dopamine pathways.